2014
DOI: 10.7314/apjcp.2014.15.19.8383
|View full text |Cite
|
Sign up to set email alerts
|

The ERCC1 C118T Polymorphism Predicts Clinical Outcomes of Colorectal Cancer Patients Receiving Oxaliplatin-Based Chemotherapy: a Meta-analysis Based on 22 Studies

Abstract: Background: Although the predictive value of the excision repair cross-complementing group 1 (ERCC1) C118T polymorphism in clinical outcomes of patients with colorectal cancer (CRC) receiving oxaliplatin-based chemotherapy has been evaluated in numerous published studies, the conclusions are conflicting. Therefore, we performed the present meta-analysis to determine the precise role of the ERCC1 C118T polymorphism in this clinical situation and help optimize individual chemotherapy. Materials and Methods: A mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 48 publications
3
11
0
Order By: Relevance
“…The Caucasian populations showed the opposite results, with significantly longer PFS and OS in patients carrying the T allele. The results of subgroup analyses were consistent with the results of previous studies [31].…”
Section: Subgroup Analysissupporting
confidence: 91%
See 1 more Smart Citation
“…The Caucasian populations showed the opposite results, with significantly longer PFS and OS in patients carrying the T allele. The results of subgroup analyses were consistent with the results of previous studies [31].…”
Section: Subgroup Analysissupporting
confidence: 91%
“…The meta-analysis results showed no correlation between Asn118Asn polymorphism and chemotherapy efficiency, PFS or OS of advanced CRC patients, which was consistent with the results of one previous meta-analysis [30]. However, recently a metaanalysis has reported correlations of ERCC1 Asn118Asn polymorphism with PFS and OS [31], and our results did not confirm it. In fact, our study also contains some advantages.…”
Section: Summary Of Meta-analysissupporting
confidence: 74%
“…The ERCC1 enzyme is involved in recognizing and removing platinum-induced intrastrand adducts in DNA; previous studies have reported that ERCC1 gene polymorphisms are associated with the response to platinum-based chemotherapy in patients with osteosarcoma, breast cancer, non-small cell lung cancer, and colorectal cancer (Bewick et al, 2011;Qian et al, 2014;Ji and He, 2015;Shi et al, 2015). Guo et al (2015) conducted a study in a Canadian population, and found that the ERCC1 rs3212986 polymorphism was not associated with the survival outcome of patients with breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Shi et al (2015) also conducted a study in a Chinese population, and found that the ERCC1 rs11615 polymorphism influences the chemotherapy and survival of patients with non-small cell lung cancer. Qian et al (2014) reported that the ERCC1 rs11615 polymorphism is associated with prognosis in colorectal cancer patients. The studies mentioned above suggest that ERCC1 gene polymorphisms are associated with prognosis in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the ERCC1 C118T SNP have focused mainly on nonsmall‐cell lung cancer and colorectal cancer . According to stratified analysis by ethnicity in a meta‐analysis, the ERCC1 118T allele was associated with a favourable prognosis in colorectal cancer in white patients, but with an unfavourable prognosis in Asian patients …”
mentioning
confidence: 99%